2021
DOI: 10.1093/jscr/rjab302
|View full text |Cite
|
Sign up to set email alerts
|

Malignant phyllodes tumor with synchronous metastases to axillary lymph nodes, lung at the presentation: a case report and literature review

Abstract: Phyllodes tumors are rare mesenchymal tumors of breast. Malignant phyllodes tumors can develop metastases to distal organs with spreading hematogenously to most frequent sites as lungs, bone and brain. Regional lymph node enlargement is common but metastasis to lymph node is a very rare phenomenon with prevalence about 1.1–3.8%. In this report, we introduce a case of malignant phyllodes tumor of breast in 57-year-old female patient. Synchronous metastases to axillary lymph nodes and lung were found at the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The definitive treatment for phyllodes tumor is wide surgical excision with at least 1-2 cm of negative margins, or mastectomy, depending on the size of the tumor and the patient's breast size. The role of adjuvant radiotherapy and chemotherapy remains unclear [27 , 28] , although some authors suggest the use of adjuvant therapy in phyllodes tumors greater than 5 cm with more than 20 mitoses per 10 high power fields because such tumors may have a high local recurrence rate [13] , and adjuvant therapy is recommended in patients with a high risk of metastasis, tumor recurrence, or the presence of metastases [29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The definitive treatment for phyllodes tumor is wide surgical excision with at least 1-2 cm of negative margins, or mastectomy, depending on the size of the tumor and the patient's breast size. The role of adjuvant radiotherapy and chemotherapy remains unclear [27 , 28] , although some authors suggest the use of adjuvant therapy in phyllodes tumors greater than 5 cm with more than 20 mitoses per 10 high power fields because such tumors may have a high local recurrence rate [13] , and adjuvant therapy is recommended in patients with a high risk of metastasis, tumor recurrence, or the presence of metastases [29] .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found a similar clinical course between pure chondrosarcoma and malignant phyllodes tumor with chondrosarcomatous differentiation [17] , while another study found that phyllodes tumors with osteosarcomatous components were potentially aggressive tumors with distant metastases, and that tumor-related death occurred in 38% of patients [31] . Distant metastasis occurs hematogeneously, with the most common sites being the lungs (66%), bones (28%), and brain (9%), while occurrence in the liver and heart being rare [28] . Since lymphatic spread is a rare phenomenon in these tumors, routine axillary lymph node dissection is not recommended [27 , 32] .…”
Section: Discussionmentioning
confidence: 99%
“…Koh et al [26] showed that a combination of large tumor size (≥90 mm) ant the presence of malignant heterologous elements had a statistically significant association with the development of distant metastasis. Most frequently, malignant PTs metastasize to the lung, bones, brain, and liver [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . Few rare distant metastatic sites are the adrenal glands [20] , kidney [13] , skin [27] , ovary [28] , heart [29] , pleura [30] , oral cavity [31] , duodenum [32] , pancreas [33] , tonsillar [12] , and para-aortic nodes [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature reports that 10%-15% of PTs are malignant and approximately 9%-27% of patients with malignant phyllodes tumor have metastasis to distant organs with spreading hematogenously to most frequent sites as lungs, bones, brain, and liver [6] . Recurrence or metastasis of breast PTs predicts a shorter survival time, less than 2 years after diagnosis [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] .…”
Section: Introductionmentioning
confidence: 99%
“…Phyl lodes tumors (PT) are rare mesenchymal tumors arising from the connective tissue of the breast. They are relatively rare, accounting for approximately 0.3%-1% of all breast tumors (1). The World Health Organization classifies PTs into 3 categories (benign, borderline, and malignant) on the basis of histopathologic features including nuclear atypia, stromal cellularity, mitotic activity, tumor margin appearance, and stromal overgrowth (2).…”
mentioning
confidence: 99%